Lack of an association of miR-938 SNP in IDDM10 with human type 1 diabetes - Mi Xiaofan; He Hongzhi; Deng Yangxin; Levin Abert M; She Jin-Xiong; Mi Qing-Sheng; Zhou Li (Diabetology & Metabolic Syndrome, 2011)
Abstract MicroRNAs (miRNAs) are a newly discovered type of small non-protein coding RNA that function in the inhibition of effective mRNA translation, and may serve as susceptibility genes for various disease developments. The SNP rs12416605, located in human type 1 diabetes IDDM10 locus, changes the seeding sequence (UGU[G/A]CCC) of miRNA miR-938 and potentially alters miR-938 targets, including IL-16 and IL-17A. In an attempt to test whether miR-938 may be a susceptibility gene for IDDM10, we assessed the possible association of the miR-938 SNP with T1D in an American Caucasian cohort of 622 patients and 723 healthy controls by TaqMan assay. Our current data do not support the association between the SNP in miR-938 and type 1 diabetes.